Combined use of alcohol and energy drinks: Dose relationship with self-reported physiological stimulation and sedation side effects. (August 2017) - Droste, Nicolas; Peacock, Amy; Bruno, Raimondo; Pennay, Amy; Zinkiewicz, Lucy; Lubman, Dan I.; Miller, Peter
Abstract: Background: Negative physiological stimulation and sedation side effects are experienced by a significant proportion of consumers who consume alcohol mixed with energy drinks (AmED). Few studies have compared the frequency of side effects between sessions of AmED and sessions of alcohol only within-subject, and none have explored a dose relationship. Objectives: Explore the occurrence of self-reported physiological stimulant and sedative side effects between sessions of AmED and alcohol only, and at varying ED dosage levels within AmED sessions. Methods: A convenience sample of 2953 residents of New South Wales, Australia completed an online survey. N = 731 AmED users reported daily caffeine intake, typical alcohol and AmED consumption, and past 12-month experience of physiological stimulation and sedation side effects during AmED and alcohol only sessions. Within-subject analyses compared occurrence of side effects between session types. Hierarchical binary logistic regression analyses explored the association of ED dose during AmED sessions with the experience of physiological side effects. Results: There were greater odds of most stimulant side effects, and lower odds of sedation side effects, during AmED sessions compared to alcohol only sessions. Compared to one ED, consumption of three or more EDs was significantly associated with the majority of both stimulant and alcohol intoxication side effects after controlling for demographics and consumption covariates. Conclusions: AmED is associated with perceived changes in physiological stimulant and sedation side effects of alcohol. Experience of side effects is positively associated with ED dosage. Future research should account for varying ED dosage, and reflect real world consumption levels. Highlights: Experience of side effects is positively associated with energy drink (ED) dosage. Greater odds of most stimulant side effects when mixing ED with alcohol Lower odds of sedation side effects when mixing ED with alcohol